2006
DOI: 10.1104/pp.106.084178
|View full text |Cite
|
Sign up to set email alerts
|

The hpa1 Mutant of Arabidopsis Reveals a Crucial Role of Histidine Homeostasis in Root Meristem Maintenance

Abstract: Histidine (His) is an essential ingredient for protein synthesis and is required by all living organisms. In higher plants, although there is considerable evidence that His is essential for plant growth and survival, there is very little information as to whether it plays any specific role in plant development. Here, we present evidence for such a role of this amino acid in root development in Arabidopsis (Arabidopsis thaliana) from the characterization of a novel Arabidopsis mutant, hpa1, which has a very sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…The loss of HISN1A function in homozygotes therefore first becomes critical during root development. Mo et al (2006) observed a similar phenotype in a weak allele (hpa1) of HISN6A and concluded that His performs an important role in root meristem maintenance. An alternative explanation is that HISN6B expression is unable to meet cellular needs for His biosynthesis in root development but can compensate more fully for a loss of HISN6A function elsewhere.…”
Section: Mutant Phenotypes and Expression Patterns Of Redundant Genesmentioning
confidence: 74%
See 2 more Smart Citations
“…The loss of HISN1A function in homozygotes therefore first becomes critical during root development. Mo et al (2006) observed a similar phenotype in a weak allele (hpa1) of HISN6A and concluded that His performs an important role in root meristem maintenance. An alternative explanation is that HISN6B expression is unable to meet cellular needs for His biosynthesis in root development but can compensate more fully for a loss of HISN6A function elsewhere.…”
Section: Mutant Phenotypes and Expression Patterns Of Redundant Genesmentioning
confidence: 74%
“…Disruption of another gene (AGD2) encoding a novel aminotransferase required for Lys biosynthesis (Hudson et al, 2006) also results in embryo lethality (Song et al, 2004). In contrast, weak alleles of HISN3 and HISN6A have a seedling phenotype Mo et al, 2006). Collections of Arabidopsis auxotrophs are not sufficiently robust at present to enable a definitive comparison of knockout phenotypes for each pathway.…”
Section: Expected Phenotypes Of Amino Acid Auxotrophsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype also distinguishes tup5-1 from other Arabidopsis mutants impaired in amino acid biosynthesis or metabolism showing defects in root growth, such as the hpa1 His biosynthesis mutant (Mo et al, 2006), the mutant Rm 57 disturbed in the Lys biosynthetic pathway (Sarrobert et al, 2000), and two mutants of the genes encoding Asp aminotransferase AspAT2, aat2-2 and aat2-T (Schultz et al, 1998;Miesak and Coruzzi, 2002). The His biosynthesis mutant hpa1 resembles tup5-1 insofar as it has a short root when grown in vitro, but there is no obvious phenotype in the aerial part and hpa1 mutants are fully fertile plants (Mo et al, 2006). Mutants for several Trp biosynthetic pathway genes are generally impaired in development under high-light but not under low-light conditions (Last et al, 1991;Radwanski et al, 1996).…”
Section: Tup5-1 Mutants Show An Unusual Blue Light-dependent Root Gromentioning
confidence: 99%
“…One such example is the characterization of a Trp biosynthesis mutant displaying a severe growth defect under high light by Last et al (1991); another one is the description of a Lys biosynthesis mutant showing altered leaf morphology and mild dwarfism by Song et al (2004). Amino acid metabolism might also influence root meristem maintenance, as well as root growth and development, as was indicated by mutants of Asp and His biosynthesis (Miesak and Coruzzi, 2002;Mo et al, 2006). It is well documented that endogenous factors controlling root growth, such as phytohormones, are often regulated by exogenous signals, for example, by water and nutrient conditions (López-Bucio et al, 2003;Monshausen and Gilroy, 2009), as well as light (Canamero et al, 2006;Tong et al, 2008).…”
mentioning
confidence: 99%